Towards rare-earth-free white light-emitting diode devices based on the combination of dicyanomethylene and pyranine as organic dyes supported on zinc single-layered hydroxide - Nyalosaso, Jeff L.; Boonsin, Rachod; Vialat, Pierre; Boyer, Damien; Chadeyron, Geneviève; Mahiou, Rachid; Leroux, Fabrice (Beilstein Journal of Nanotechnology, 2019)
A new luminescent composite film resulting from the dispersion of luminescent organic dyes in a single-layered hydroxide (SLH)-type inorganic matrix has been developed. Two fluorescent organic dyes emitting visible light upon blue LED excitation were investigated in this study: dicyanomethylene (DCM) and pyranine (HPTS). These dyes exhibit broad emission bands that cover a large part of the visible spectrum. The concept developed in our work consisted in keeping SLH in its wet form to ensure a good dispersion of the fluorescent dyes prior to immobilizing the hybrid materials in a silicone polymer to achieve luminescent composite films. We demonstrate that these coatings stacked upon each other and placed above a blue LED lead to white-light emission with suitable photometric parameters for applications in lighting or display devices: colour temperature of 5409 K and colour rendering index (CRI) of 81.
Keywords: dicyanomethylene (DCM); hybrid luminescent films; light-emitting diode (LED); pyranine; zinc hydroxyacetate

(untitled) - Piquette, A.; Bergbauer, W.; Galler, B.; Mishra, K. C. (ECS J. Solid State Sci. Technol., 2016)

(untitled) - Wang, M.-S.; Guo, G.-C. (Chem. Commun., 2016)

(untitled) - Mondal, T.; Mondal, S.; Bose, S.; Sengupta, D.; Ghorai, U. K.; Saha, S. K. (J. Mater. Chem. C, 2018)

JRC-scientific and strategic reports - Moss, R.; Tzimas, E.; Kara, H.; Willis, P.; Kooroshy, J. (Critical metals in strategic energy technologies- Assessing Rare Metals as Supply-Chain Bottlenecks in Low-Carbon Energy Technologies, 2011)

(untitled) - Alonso, E.; Sherman, A. M.; Wallington, T. J.; Everson, M. P.; Field, F. R.; Roth, R.; Kirchain, R. E. (Environ. Sci. Technol., 2012)

(untitled) - Hatch, G. P. (Elements, 2012)

(untitled) - Boonsin, R.; Chadeyron, G.; Roblin, J.-P.; Boyer, D.; Mahiou, R. (J. Mater. Chem. C, 2016)

(untitled) - Marangoni, R.; Bouhent, M.; Taviot-Guého, C.; Wypych, F.; Leroux, F. (J. Colloid Interface Sci., 2009)

(untitled) - Sun, Z.; Jin, L.; Shi, W.; Wei, M.; Duan, X. (Chem. Eng. J., 2010)

(untitled) - Aloisi, G. G.; Costantino, U.; Latterini, L.; Nocchetti, M.; Camino, G.; Frache, A. (J. Phys. Chem. Solids, 2006)

(untitled) - Quites, F. J.; Germino, J. C.; Atvars, T. D. Z. (Colloids Surf., A, 2014)

(untitled) - Lee, J. H.; Jung, D.-Y.; Kim, E.; Ahn, T. K. (Dalton Trans., 2014)

Evaluation of IN SITU synthesis route of layered hydroxides in the presence of amphiphilic polymers in comparison with their corresponding physical mixtures - Langry, A. (Université Blaise Pascal, 2015)

(untitled) - Poul, L.; Jouini, N.; Fiévet, F. (Chem. Mater., 2000)

(untitled) - Poul, L.; Ammar, S.; Jouini, N.; Fievet, F.; Villain, F. (J. Sol-Gel Sci. Technol., 2003)

(untitled) - Coronado, E.; Galán-Mascarós, J. R.; Gómez-García, C. J.; Laukhin, V. (Nature, 2000)

(untitled) - Zhang, Y.; He, B.; Liu, J.; Hu, S.; Pan, L.; Zhao, Z.; Tang, B. Z. (Phys. Chem. Chem. Phys., 2018)

(untitled) - Rogez, G.; Massobrio, C.; Rabu, P.; Drillon, M. (Chem. Soc. Rev., 2011)

(untitled) - Moezzi, A.; McDonagh, A.; Dowd, A.; Cortie, M. (Inorg. Chem., 2013)

(untitled) - Bruckbauer, J.; Brasser, C.; Findlay, N. J.; Edwards, P. R.; Wallis, D. J.; Skabara, P. J.; Martin, R. W. (J. Phys. D: Appl. Phys., 2016)

(untitled) - Singh, G.; Mehta, D. S. (J. Inf. Disp., 2014)